2015
DOI: 10.1371/journal.pone.0143568
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Pigeon (Columba) Ovary Transcriptomes to Identify Genes Involved in Blue Light Regulation

Abstract: Monochromatic light is widely applied to promote poultry reproductive performance, yet little is currently known regarding the mechanism by which light wavelengths affect pigeon reproduction. Recently, high-throughput sequencing technologies have been used to provide genomic information for solving this problem. In this study, we employed Illumina Hiseq 2000 to identify differentially expressed genes in ovary tissue from pigeons under blue and white light conditions and de novo transcriptome assembly to constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Therefore, these genes might play important roles during chicken growth and development. Interestingly, GAPDH gene, one of the most commonly used housekeeping gene [ 33 , 34 ], was identified as a DEG in this study because of its significantly lower expression level at 16 weeks of age than at 4 and 12 weeks of age. And in some other previous studies [ 35 , 36 ], it was shown that the expression of GAPDH were not always stable in different tissues or under different experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these genes might play important roles during chicken growth and development. Interestingly, GAPDH gene, one of the most commonly used housekeeping gene [ 33 , 34 ], was identified as a DEG in this study because of its significantly lower expression level at 16 weeks of age than at 4 and 12 weeks of age. And in some other previous studies [ 35 , 36 ], it was shown that the expression of GAPDH were not always stable in different tissues or under different experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Target prediction and functional analysis of these genes, including ENSGALT00000099549, ENSGALT00000103341, ENSGALT00000097648, XR_001468386.1, XR_003077640.1, and XR_001464460.2, showed that many lncRNA target mRNAs were associated with steroid hormone biosynthesis, ovarian steroidogenesis, TGF-β signaling pathway, prolactin signaling pathway, MAPK signaling pathway, estrogen signaling pathway, PI3K-Akt signaling pathway, Hippo signaling pathway, MAPK signaling pathway, and cell adhesion molecules. In our previous studies, steroid hormone biosynthesis and the PI3K-Akt signaling pathway were also altered in pigeons under monochromatic light (Wang et al, 2015 , 2019 ). Huang et al ( 1979 ) suggested that progesterone is synthesized by GCs, and Hu et al ( 2017 ) concluded that PI3K and AMPK signaling pathways converge to modulate ERK activity, and thereby regulate GC differentiation.…”
Section: Discussionmentioning
confidence: 84%
“…After total RNA was reverse-transcribed, quantitative real-time PCR (qRT-PCR) was performed on an ABI 7500 thermocycler (Applied Biosystems). The GAPDH (glyceraldehyde-3-phosphate dehydrogenase) was used as the internal reference gene for normalization of expression data ( Wang Y. et al 2015 ). Primers used in the present study are listed in Supplemental Material, Table S1 .…”
Section: Methodsmentioning
confidence: 99%
“…The development of the RNA-Sequencing (RNA-Seq) technique has opened new opportunities for researchers to obtain huge amounts of information about the transcriptome profile of tissues of interest, which help in the acquisition of knowledge concerning the mechanism of lipid deposition in livestock ( Jeong et al 2013 ; Chen et al 2015 ; Wang Z. et al 2015 ; Miao et al 2015 ). To our best knowledge, there are no data available in the literature regarding the gene expression profiles in the muscle and liver tissues of squabs.…”
mentioning
confidence: 99%